Compreendendo as dimensões da governança pública: um estudo de caso na Câmara de Vereadores de Tangará da Serra, Mato Grosso (MT) - Terra, Josenai Oliveira (2023)
The search for a more effective public administration imposes the need to involve citizens in the decision-making process of public policies. With this, in a macro perspective, generate information on the disclosure of the dimensions of the New Public Governance (NPG) which can contribute to the development of strategies that meet the demands that citizens impose on management, something that until then has been little implemented by existing models. public administration in the legislature. Thus, this work aims to raise dimensions for the analysis of NPG, still lacking in the literature. As demonstrated, the dimensions are: deliberative democracy, co-production, public value, displacement of power, coordination, efficiency and effectiveness and accountability. The aim is to understand how governance structures and processes are organized for the construction of public policies in the City Council of Tangará da Serra, in Mato Grosso, and then seeks to verify the different aspects of the concept of public governance. By examining the meaning of its principles, as a subsidy for the State's social control, it aims to identify, in the analysis model, its mechanisms, in the dimensions of public governance applied with the City Council. The challenge for the Legislature is to build a drafting process that is more inclusive and aware of the role of citizens. This change is of a cultural nature, as it involves the transformation of values and behaviors rooted in municipal public power, and if it is true that the rulers are a representation of the society they govern. The research approach method used in this study is characterized as a case study, being qualitative, bibliographical research, interviews with the legislature, executive, class bodies, descriptive approach, participant observation through sessions and public hearing, documental analysis of minutes and law Municipal organization in the projects/laws, thus allowing to analyze them in the study. In this way, the results allowed the identification of relevant aspects of the categories of analysis of the New Public Governance. The study contributes to greater democracy, coparticipation, transparency and legitimacy in the construction of processes and their implementation, thus ensuring quality of life for the population and greater effectiveness in public policies.